Patterns associated with hunting with dogs in a semiarid region of northeastern Brazil - Sebastiana Lima Santos; María Fernanda De la Fuente; Rômulo Romeu Nóbrega Alves (BMC, 2022)
Abstract Background Hunting has been an important cultural and subsistence activity for the survival of the human population. In the Brazilian semiarid region (Caatinga), the extreme seasonal changes and socioeconomic conditions have made local people dependent on the natural resources available, including wildlife. Although hunting with dogs can result in higher efficiency for hunters, it can also have implications for game species conservation. Methods Using an ethnozoological approach (semi-structured questionnaires, free interviews, informal conversations, and free listing technique), this study aimed to analyze the patterns of hunting with dogs activities in a semiarid region of northeastern Brazil by characterizing hunters' and hunting dogs' profiles, investigating target and nontarget prey species, hunters' practices, motivations, and perceptions regarding the efficiency of hunting with dogs. Results We found that hunters that use dog assistance were mostly men, of different ages, with an occupation in agriculture, receiving less than a minimum wage, and with a low level of formal education. Hunters use two or more mixed-breed dogs with no clear preference regarding dogs' sex. The motivations for hunting with dogs included mainly food, sport, and trade. Hunters cited twenty species captured by dogs without distinction between prey's sex and age (14 mammals, 4 birds, and 2 reptiles). Only six of these were mentioned as being target prey when hunting with dogs. From nontarget species, eight carnivores are usually left at the site of kill, as they have no use to the hunters. Hunters perceived that hunting with dogs could be three times more efficient than hunting without dogs. Conclusion Overall, hunting with dogs represents a complex set of local variables, including characteristics of dogs and prey species, hunters' motivations, and practices that should be considered according to each particular situation. Considering the human dependence on natural resources in the semiarid region, hunters should be included in wildlife management debates to mitigate the threat to game species while allowing sustainable hunting practices.